Features of the atherosclerotic plaque microbiome in patients after carotid endarterectomy - E. P. Kolesova; M. A. Chernyavsky; A. G. Vanyurkin; E. V. Verkhovskaya; E. K. Zaykova; O. V. Kalinina; S. I. Sitkin; A. L. Maslyansky; V. V. Kvan; E. Yu. Vasilyeva; A. N. Yakovlev; A. Yu. Babenko; et al. (Российский кардиологический журнал, 2025)
Aim. To study the microbiome of atherosclerotic plaque biopsies in patients who underwent carotid endarterectomy (CEA).Material and methods. In this study, the microbiota profile of 76 atherosclerotic plaque samples obtained during CEA was analyzed using high-throughput sequencing of 16S rRNA V4 region. The proportion of patients without restenosis included in the study was 20%. The median follow-up of patients was 1,9 years (range, 1,4-2,25).Results. Taxonomic analysis revealed that the plaque microbiome is characterized by a wide diversity of gram-negative bacteria, including bacteria that are widespread in the environment. Bacteria most represented in plaques belong to four following families: Caulobacteraceae, Rhizobiaceae, Sphingobacteriaceae and Weeksellaceae. Linear discriminant analysis Effect Size (LEfSe) revealed a significantly higher representation of the microbial marker OTU_21, belonging to the Sphingomonadaceae family, in the atherosclerotic plaque microbiome of patients with ≥50% restenosis and Cloacibacterium (OTU_67), belonging to the Weeksellaceae family, in patients with >70% restenosis.Conclusion. The obtained data emphasize the importance of studying the atherosclerotic plaque microbiome and suggest that microorganisms of various origins, including those that have not previously been considered as risk factors, can play a pathogenetic role in both atherogenesis and restenosis.